Pengembangan Media Number Spinning Wheel pada Materi Calistung di Kelas 1 UPT SD Negeri 63 Gresik - Salma Hikmahtul Nur Rochmah; Iqnatia Alfiansyah (Journal on Education, 2023)
Thematic is a learning that covers all aspects and some materials in a lesson, one of them is mathematics. Where learning mathematics is very important in the daily lives of students. Calistung (reading, writing, and counting) material is one of the lessons in mathematics. Using this rotary wheel media can increase students' abilities, interests and creativity in reading, writing and arithmetic materials. Therefore, to understanding the ability to reading, writing, and counting in students is something that is necessary and very important. This study aims to determine the development of Number Spinning Wheel learning media on class 1 calistung material at UPT SD Negeri 63 Gresik.The results of the media expert validation obtained 92.8% which stated that this media was categorized as valid and from the material experts obtained a value of 87.5% which also stated that this media was valid, so it can be concluded that the number spinning wheel media met the valid criteria and effectively used in continous learning.